A Swarm Optimization approach for clinical knowledge mining. Issue 3 (October 2015) - Christopher, J. Jabez; Nehemiah, H. Khanna; Kannan, A.
Highlights Wind-driven Swarm Optimization (WSO) is used for optimizing the rule base of a Clinical Decision Support System. WSO is a bio-inspired approach inspired from the flight of birds. WSO uses Jval to evaluate the efficiency of a rule based CDSS. Experiments with six medical datasets show that WSO provides efficient rulesets. The novelty of WSO lies in its biological motivation and customization for rule base optimization.